Unveiling the Impact of Statin Drugs on Liver Enzyme Variation in COVID-19 Patients in Baghdad, Iraq - Alkilidar, Osamah; Albaghdadi, Hayder; kh.alhashimi, Samaa (South Eastern European Journal of Public Health, 2024)
Recent studies have examined the safety of using statin drugs in COVID-19 patients and have suggested that their anti-inflammatory properties may help lessen the severity of the infection and speed up recovery. However, some case reports have indicated that COVID-19 patients taking statins may experience liver injury, a serious adverse effect of the medication. To investigate this further, a study was conducted on 140 patients who were divided into four groups: those infected with SARS-CoV2 while taking statins, those infected without taking statins, those not infected but taking statins, and healthy individuals serving as a control. The results indicate that statins have a significant effect on AST and ALP levels but not on ALT levels, suggesting that the medication does not have a statistically significant impact on liver function..